Effects of short-wave light on anaerobic performance - Beaven, C.; Ekström, J. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Overview Short-wavelength light (450-495nm) is perceived by humans as blue and is known to stimulate biological functions. Blue light interventions enhance cognitive function and reaction times (Beaven & Ekström, 2013) and affect brain areas associated with arousal and circadian rhythmicity (Rautkylä, Puolakka, & Halonen, 2011). Exposure to short-wavelength light has been reported elevate testosterone and increase lean muscle mass (Cao et al., 2008). Testosterone has been suggested to be acutely linked to power production (Crewther, Cook, Cardinale, Weatherby, & Lowe, 2011). Hence, we investigated whether exposure to short-wavelength light could impact performance in an anaerobic power test. Methods: 21 healthy volunteers performed a 30s Wingate test on a Monark friction-braked ergometer against a resistance of 0.075kg/kgBW immediately following a 60min exposure to either a blue LED light source (470 nm) or a white light alternative. Relative peak, average, and minimum power data was collected, as well as percentage power decrease. Results: There were no differences between the peak power or average power but the minimum power was clearly higher in the blue light condition (5.53 vs. 4.99W/kg; Effect Size: 0.49±0.59). As a result, the power decrease was lesser in the blue light condition (50.7 vs. 55.6%; Effect Size: 0.39±0.59). Conclusions: It was apparent that the 60min exposure to blue LED lighting was capable of improving fatigue resistance exercise performance in a test of anaerobic power. While the mechanism is unclear, there is potential for short-wavelength light to manipulate athletic performance via direct visual input to the limbic and arousal system.